The effect of CO2 laser beam welded AISI 316L austenitic stainless steel on the viability of fibroblast cells, in vitro - Kose, Ceyhun; Kacar, Ramazan; Zorba, Asli Pinar; Bagirova, Melahat; Allahverdiyev, Adil M. (ELSEVIER SCIENCE BV, 2016)
It has been determined by the literature research that there is no clinical study on the in vivo and in vitro interaction of the cells with the laser beam welded joints of AISI 316L biomaterial. It is used as a prosthesis and implant material and that has adequate mechanical properties and corrosion resistance characteristics. Therefore, the interaction of the CO2 laser beam welded samples and samples of the base metal of AISI 316L austenitic stainless steel with L929 fibroblast cells as an element of connective tissue under in vitro conditions has been studied. To study the effect of the base metal and the laser welded test specimens on the viability of the fibroblast cells that act as an element of connective tissues in the body, they were kept in DMEMF-12 medium for 7, 14, 28 days and 18 months. The viability study was experimentally studied using the MTF method for 7, 14, 28 days. In addition, the direct interaction of the fibroblast cells seeded on 6 different plates with the samples was examined with an inverted microscope. The MIT cell viability experiment was repeated on the cells that were in contact with the samples. The statistical relationship was analyzed using a Tukey test for the variance with the GraphPad statistics software. The data regarding metallic ion release were identified with the ICP-MS method after the laser welded and main material samples were kept in cell culture medium for 18 months. The cell viability of the laser welded sample has been detected to be higher than that of the base metal and the control based on 7th day data. However, the laser welded sample's viability of the fibroblast cells has diminished by time during the test period of 14 and 28 days and base metal shows better viability when compared to the laser welded samples. On the other hand, the base metal and the laser welded sample show better cell viability effect when compared to the control group. According to the ICP-MS results of the main material and laser welded samples which were kept in the cell culture medium for 18 months, it was determined that the Fe, Ni and Cr ion concentration released to the cell culture medium from the laser welded test sample was less than that of the main material. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Laser beam welding; Austenitic stainless steel; L929 fibroblast cell; Viability; Tukey test; MECHANICAL-PROPERTIES; CORROSION BEHAVIOR; LASER; SURFACE; NITROGEN; MICROSTRUCTURE; CYTOTOXICITY; Materials Science